The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.5811/westjem.2013.3.15705
|View full text |Cite
|
Sign up to set email alerts
|

Co-Occurring Physical Fighting and Suicide Attempts among U.S. High School Students: Examining Patterns of Early Alcohol Use Initiation and Current Binge Drinking

Abstract: Introduction: A growing body of empirical research documents a significant co-occurrence of suicide attempts and interpersonal violence among youth. However, the potential role of early alcohol use initiation and current heavy alcohol use as correlates of this comorbidity has not been examined in a nationally representative sample of high school students.Methods: We based our analyses on cross-sectional data from the 2009 Youth Risk Behavior Survey, which includes a nationally representative sample (n=16,410) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 25 publications
2
13
0
Order By: Relevance
“…Findings from the present study indicate that alcohol, marijuana, and other DUD criteria and nicotine dependence are significantly related to violence toward others and self. They are consistent with the findings from general population studies of violence toward others (Coid et al, 2006;Corrigan & Watson, 2005;Pulay et al, 2008) and toward self (Borowsky et al, 2001;Harris & Barraclough, 1997;Roy et al, 1990) and, more importantly, expand on the findings from prior studies for combined (Bossarte et al, 2008;Cleary, 2000;Harford et al, 2012;Swahn et al, 2013). Nevertheless, comparisons between the violence categories show that the increased number of marijuana use disorder criteria was no longer a significant predictor to discriminate one form of violence from another.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Findings from the present study indicate that alcohol, marijuana, and other DUD criteria and nicotine dependence are significantly related to violence toward others and self. They are consistent with the findings from general population studies of violence toward others (Coid et al, 2006;Corrigan & Watson, 2005;Pulay et al, 2008) and toward self (Borowsky et al, 2001;Harris & Barraclough, 1997;Roy et al, 1990) and, more importantly, expand on the findings from prior studies for combined (Bossarte et al, 2008;Cleary, 2000;Harford et al, 2012;Swahn et al, 2013). Nevertheless, comparisons between the violence categories show that the increased number of marijuana use disorder criteria was no longer a significant predictor to discriminate one form of violence from another.…”
Section: Discussionsupporting
confidence: 81%
“…Using a similar typology, Swahn et al (2013) found significant associations between combined violence (physical fighting and suicide attempt) and early drinking onset, heavy drinking, and feelings of sadness. Drinking onset before age 13 versus nondrinkers was significantly related to violence but not significantly different among different patterns of violence.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Among high school students, the prevalence of physical fighting can be as high as 31.5% (Swahn, Bossarte, Palmier, & Yao, 2013). As such, including this item may have produced a higher base rate of violent offending compared to some other studies.…”
Section: Discussionmentioning
confidence: 92%
“…In general, EAU has been associated with a host of maladaptive outcomes, including alcohol problems and sexual risk-taking (Stueve and O'Donnell 2005), as well as lower education attainment (Grant et al 2012). It has also been linked more specifically to increased risk for SA (Bossarte and Swahn 2011;Swahn et al 2010;Swahn and Bossarte 2007) and comorbid reports of SA and physical fighting among high school students (Swahn et al 2013). Far fewer studies have examined EAU and NSSI.…”
mentioning
confidence: 99%